2005
DOI: 10.1002/app.21993
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of 2‐diethyl‐aminoethyl–dextran–methyl methacrylate graft copolymer for nonviral gene delivery vector

Abstract: ABSTRACT:A stable and soapless latex of 2-diethyl-aminoethyl (DEAE)-dextran-methyl methacrylate (MMA) graft copolymer (DDMC) was developed for nonviral gene delivery vectors (complex between polycation and nucleic acid). DDMC was newly prepared using MMA and DEAE-dextran. Following a transfection protocol, transfection of HEK 293 cells by DDC1, DDC2, and DDC3 samples was carried out using plasmid DNA. With the transfection efficiency determined using the X-Gal staining method, a higher value of 5 times or more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 22 publications
(22 reference statements)
0
10
1
Order By: Relevance
“…When comparing transfection efficiency for DEAE-dextran (graft ratio 0%) and DDMC in transfection experiments carried out using HEK293 cells, remarkable results, to have an amphiphilic domain in order to form a polymer micelle, were obtained with DDMC (graft ratio 130%) [5,6,7,8,9]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When comparing transfection efficiency for DEAE-dextran (graft ratio 0%) and DDMC in transfection experiments carried out using HEK293 cells, remarkable results, to have an amphiphilic domain in order to form a polymer micelle, were obtained with DDMC (graft ratio 130%) [5,6,7,8,9]. …”
Section: Resultsmentioning
confidence: 99%
“…Although these compounds have problems with cytotoxicity and low transformation rates, they have a history of use as nonviral vectors, and desirable DEAE-dextrans (2-diethylaminoethyl-dextran) are currently being closely investigated because they can be sterilized [3,4]. Copolymers formed by graft polymerization of methyl methacrylate (MMA) with DEAE-dextran have hydrophilic and hydrophobic regions and are known to be desirable non-viral vectors due to their high transformation efficiency [5,6,7]. Thus, complexes of DNA and DEAE-dextran-MMA graft copolymer (DDMC) produced by modification of DEAE-dextran has been reported to have superior transformation efficiency of 50× or more relative to DEAE-dextran in terms of transformation efficiency in various types of cell [8].…”
Section: Introductionmentioning
confidence: 99%
“…Characteristics of the 2-diethylaminoethyl-dextran methyl methacrylate graft copolymer: DDMC is a copolymer that is formed through grafting MMA onto DEAE–dextran as the backbone polymer by using a tetravalent ceric salt [14]. It generates a polymer micelle that forms a microphase-separated structure with a hydrophilic domain for the DEAE–dextran part and a hydrophobic domain for the graft polymer PMMA.…”
Section: Reviewmentioning
confidence: 99%
“…That is, from Fig. 1, the absorbance variation of DEAE–dextran/DNA is large, so that there is a large amount of toluidine blue because the decomposition of DNA by DNase is promoted in the presence of DEAE–dextran/DNA from the earliest stage [15]. Conversely, for DDMC/DNA, the DNA decomposition hardly progressed, but the absorbance variation was very small.…”
Section: Reviewmentioning
confidence: 99%
“…The resulting DDMC consists of 'hairy' nanoparticles with an amphiphilic domain (DEAE-dextran) and a hydrophobic domain (MMA polymer, PMMA) that form a polymer micelle [11]. It has been reported that DDMC is superior to other transfection with safety transfection efficacy by autoclaved as a non-viral carrier for gene introduction [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%